The Translation of Reiteration - Astiari, Komang; Budiarta, I Wayan; Pratama, Agus Darma Yoga (RETORIKA: Jurnal Ilmu Bahasa, 2019)
Lexical cohesion has been a serious issue as it is one of the important features in a text. Every writer must consider kinds of lexical devices in writing a text and so do the translator. The main problem in translating the lexical cohesion devices is the different structure between two languages. One device can be applied in one language but not in other language. This journal analyzed the translation of reiteration as part of lexical cohesion devices appeared in the short stories The Black Cat and The Cask of Amontillado written by American writer, Edgar Allan Poe. The short stories were translated by two Indonesian translators namely Anton Kurnia and Shinta Dewi. This research is conducted to share the practice of translating literature works especially a short story which contains a lot of lexical cohesion devices and to give contribution to the development of translation as part of linguistic studies. In doing the research, qualitative and quantitative method is applied including observation, interviews, or document reviews. In the source text, it was found 120 of lexical cohesion devices in the short story â€The Cask of Amontilladoâ€ and 187 lexical cohesion devices in the short story â€œThe Black Catâ€. The results obtained from this research were that Anton Kurnia translated 73% of lexical cohesion devices in the source language into the target language. Meanwhile, Shinta Dewi translated 94% of lexical cohesion devices in the source text to the target text.